A complex type smoke-suppressing green flame retardant and flame-retardant plywood prepared therefrom
By using complexed smoke-resisting green flame retardant, the problems of traditional flame retardant pollution and wood flammability are solved, and efficient and environmentally friendly flame retardant effects are achieved.
Patent Information
- Application Number
- CN202411850935.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-04
AI Technical Summary
Traditional flame retardants may contaminate the environment during use, and the flammability of wood limits its application in certain fields.
Complexed smoke-repressing green flame retardant is used, which consists of modified ammonium polyphosphate, MOF, metal-modified molecular sieve, etc., and is combined with wood through chemical bonding to form a stable flame retardant structure.
It significantly improves the flame retardant performance of wood, reduces smoke and toxic gas emissions in fires, and does not contain harmful substances, and is environmentally friendly.
Smart Images

Figure CN119748582A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a new material, in particular to a complex type smoke suppressing green flame retardant and a flame retardant plywood prepared therefrom. Background Art
[0002] As a traditional building material and furniture manufacturing material, wood has the advantages of light weight, high strength and good processing performance, but its flammability limits its application in some fields. In order to improve the flame retardant properties of wood, people have developed a variety of flame retardants and technologies. Complex smoke-suppressing green flame retardants combine flame retardant elements with functional groups in wood through chemical bonding to form a stable flame retardant structure, thereby significantly improving the flame retardant properties of wood. This flame retardant can not only effectively reduce the burning speed of wood, but also reduce the emission of smoke and toxic gases in fires, and improve the safety of escape and rescue.
[0003] With the increasing awareness of environmental protection, people have put forward higher requirements for the environmental performance of building materials and furniture. Traditional flame retardants often contain harmful substances such as halogens and phosphorus, which may cause pollution to the environment during use. The complex type smoke suppression green flame retardant is prepared with non-toxic and harmless raw materials, and will not cause pollution to the environment during use; flame retardant plywood is made by peeling wood segments into veneers or planing wood blocks into veneers, and then gluing the veneers with adhesives after flame retardant treatment. Since flame retardant plywood has excellent flame retardant and environmental performance, it can be used in more fields that require fire prevention and environmental protection.
[0004] As people's pursuit of quality of life and safety continues to improve, the market demand for flame-retardant plywood is also increasing. The preparation of a complex smoke-suppressing green flame retardant and flame-retardant plywood prepared therefrom can meet the market demand for high-quality, high-performance building materials and furniture, and improve the market competitiveness of products. Summary of the invention
[0005] In view of the above problems, the present invention provides a complex type smoke-suppressing green flame retardant and a flame-retardant plywood prepared therefrom.
[0006] The present invention provides a complex type smoke suppression green flame retardant and a flame retardant plywood prepared therefrom, comprising the following steps: step (1) synthesis of MOF, step (2) synthesis of ammonium polyphosphate, step (3) synthesis of diaminodiphenylmethane modified ammonium polyphosphate, step (4) modification of 5A molecular sieve, step (5) complex type smoke suppression green flame retardant, step (6) preparation of flame retardant and smoke suppression hollow board core, step (7) preparation of tannin-formaldehyde-furfural resin adhesive, and step (8) preparation of flame retardant plywood; Wherein, the preparation steps of the complex type smoke suppression green flame retardant in step (5) include: The ammonium polyphosphate modified in step (3) and the MOF prepared in step (1) are added to deionized water and stirred thoroughly until no precipitation is produced; then the metal-modified molecular sieve, MC and 500Cu-Z prepared in step (4) are added in sequence and further stirred until no precipitation is produced, thereby obtaining a complex-type smoke-suppressing green flame retardant.
[0007] Preferably, step (1) synthesis of MOF Dissolve zinc nitrate hexahydrate, tetrachloroterephthalic acid, triethylenediamine and DMF together in a transparent glass bottle, place it in an oven and heat it at a constant temperature to obtain colorless rhombus crystals; Step (2) Synthesis of ammonium polyphosphate Phosphoric acid and urea are added to a three-necked flask and heated and stirred. When the temperature reaches the prepolymerization temperature, the urea is completely melted and the solution is clear and bubbling, and a large amount of gas escapes. When the solution becomes thick and sticky, it is discharged into a white porcelain plate under continuous stirring and placed in a constant temperature oven for polymerization and curing. After the curing is complete, it is cooled to obtain ammonium polyphosphate; Step (3) Synthesis of diaminodiphenylmethane modified ammonium polyphosphate Mix ethanol and water and pour them into a three-necked flask. Heat the mixed solution in an oil bath to a certain temperature and stir. Then, inject molten DDM into the mixed solution. Slowly inject the ammonium polyphosphate prepared in step (2) into the three-necked flask. After the stirring reaction is completed, cool the mixed solution and filter to obtain a light yellow solid. Wash it with distilled water and ethanol respectively, and then dry it. Grind and sieve the obtained light yellow solid to obtain diaminodiphenylmethane modified ammonium polyphosphate. Step (4) Modification of 5A molecular sieve Grind polyphosphoric acid and 5A molecular sieve in ceramic mortars respectively until fully uniform. After activation in a muffle furnace, add wood powder and continue grinding until fully uniform for use. Metal ion modified molecular sieve: soak the molecular sieves in aqueous solutions of different metal salts respectively, stir and sand grind them with a sand grinder / dispersing stirring multi-purpose machine, let them air dry naturally, and then place them in a muffle furnace for roasting to obtain the metal modified molecular sieve.
[0008] Step (5) Complex type smoke suppression green flame retardant Add the ammonium polyphosphate modified in step (3) and the MOF prepared in step (1) into deionized water and stir thoroughly until no precipitation is produced; then add the metal-modified molecular sieve, MC and 500Cu-Z (copper-modified molecular sieve) prepared in step (4) in sequence and stir further until no precipitation is produced to obtain a complex-type smoke-suppressing green flame retardant; Step (6) Preparation of flame retardant and smoke suppression hollow board core The veneer is impregnated with the complex type smoke suppression green flame retardant prepared in step (5) and then dried. The veneer after drying is then mixed with deionized water, the complex type smoke suppression green flame retardant and molecular sieve to prepare a flame retardant and smoke suppression board core. The mixture is stirred in a stirrer to be fully dispersed. The mixture is placed in a vacuum drying oven and dried until no water overflows. The dried mixture is cold pressed in a mold to prepare a board core. Step (7) Preparation of tannin-formaldehyde-furfural resin adhesive Dissolve tannin powder in sodium hydroxide solution to prepare tannin solution, then heat the tannin solution in a three-necked flask; add sodium sulfite to the mixed solution in the three-necked flask, keep warm, add formaldehyde solution and furfural pretreatment solution to the tannin pretreated solution, keep warm; cool the tannin solution quickly, and then produce glue to obtain tannin-formaldehyde-furfural resin adhesive.
[0009] Preferably, step (1) synthesis of MOF Dissolve zinc nitrate hexahydrate (7.0-7.5 mg, 0.025-0.030 mmol), tetrachloroterephthalic acid (10-13 mg, 0.04-0.08 mmol), triethylenediamine (2.0-3.0 mg, 0.02-0.05 mmol) and DMF (1.0-2.0 mL) in a 15-22 mL transparent glass bottle, place in an oven at 83-86 ° C and heat at a constant temperature for 1-5 days to obtain colorless rhombus crystals.
[0010] The invention has the advantages that zinc nitrate hexahydrate provides metal nodes in the MOF framework, and tetrachloroterephthalic acid coordinates with metal ions to form the MOF framework; chlorine atoms can be arranged in the pores of the MOF as functional groups to regulate the interaction between the MOF and the gas and enhance the stability of the MOF.
[0011] Preferably, step (2) the synthesis of ammonium polyphosphate 82-86% phosphoric acid and 98-99% urea are sequentially added into a three-necked flask at a ratio of 1-2:1.7-1.8 (molar ratio), heated and stirred, and the heating rate is controlled to be no more than 5-10°C / min. When the temperature reaches the prepolymerization temperature (about 95-100°C), the urea is completely melted and the solution is clear and bubbling, and a large amount of gas escapes (early pH=3-6 and later pH=8-10). After the solution becomes thick and sticky, it is discharged into a white porcelain plate under continuous stirring and placed in a constant temperature oven for polymerization and curing. After the curing is complete, it is cooled to obtain ammonium polyphosphate.
[0012] The invention has the advantages that the heating speed can be controlled to avoid local overheating or reaction runaway caused by overly fast heating, thereby ensuring the smooth progress of the reaction; the prepolymerization temperature control is conducive to the complete melting of urea and avoids possible side reactions at high temperatures; the material is discharged into a white porcelain dish under continuous stirring, thereby ensuring the uniformity and fluidity of the solution and facilitating the progress of polymerization and curing.
[0013] Preferably, step (3) the synthesis of diaminodiphenylmethane modified ammonium polyphosphate Mix ethanol and water (195-200ml:10-12ml) and pour them into a three-necked flask. Heat the mixed solution in an oil bath to 85-90°C and stir for 30-35min. Then, inject 10-13g of molten DDM into the mixed solution. Slowly inject 20-24g of the ammonium polyphosphate prepared in step (2) into the three-necked flask and stir at 58-62°C for 3-5h. After the reaction is completed, cool the mixed solution and filter to obtain a light yellow solid. Wash it with distilled water and ethanol for 1-3 times respectively, and then dry it at 60-65°C. Grind and sieve the obtained light yellow solid to obtain diaminodiphenylmethane modified ammonium polyphosphate.
[0014] The invention has the advantages that the mixed solution of ethanol and water as a solvent not only provides a good reaction environment, but also helps to evenly mix the raw materials. The oil bath heating ensures the full melting and dispersion of DDM. Meanwhile, the reaction conditions are also conducive to the ion exchange reaction between APP (ammonium polyphosphate) and DDM, while avoiding the side reaction that may occur at high temperature. DDP (diaminodiphenylmethane modified ammonium polyphosphate) shows excellent flame retardant properties in epoxy resin, and adding a small amount of DDP can significantly reduce the flammability of epoxy resin.
[0015] Preferably, step (4) modification of 5A molecular sieve Place polyphosphoric acid and 5A molecular sieve in a ceramic mortar and grind for 24-30 minutes respectively, grind thoroughly, pass through a 100-120 mesh sieve, activate in a muffle furnace at 795-800°C for 6-10 hours, add wood powder and continue grinding until it is fully uniform for use. Metal ion modified molecular sieve: soak the molecular sieve in aqueous solutions of different metal salts (the metal element loading is 1-5% of the mass of the molecular sieve), stir for 1-2 hours, then sand grind with a sand grinder / dispersing stirring multi-purpose machine for 30-35 minutes, place it to air dry naturally, dry at 100-110°C for 1-4 hours, and then place it in a muffle furnace at 550-555°C for calcination for 10-12 hours to obtain a metal modified molecular sieve.
[0016] The advantages of the present invention are that the acidity and adsorption performance of the 5A molecular sieve can be enhanced by grinding and activating the polyphosphoric acid, so that it has higher selectivity and adsorption capacity for specific substances, and the introduction of metal ions can further improve the structural stability of the molecular sieve; the introduction of polyphosphoric acid and metal ions can significantly improve the thermal stability and chemical stability of the 5A molecular sieve, so that it can still maintain good performance in a high temperature environment.
[0017] Preferably, step (5) comprises a complex type smoke suppressing green flame retardant Add 25-30g of the ammonium polyphosphate modified in step (3) and the MOF prepared in step (1) into 95-100mL of deionized water, and stir thoroughly at 30-35°C until no precipitation is produced; then add the metal-modified molecular sieve prepared in step (4), 0.6-0.8g of MC (sodium carboxymethyl cellulose) and 0.5-0.9g of 500Cu-Z (copper-modified molecular sieve), and further stir until no precipitation is produced to obtain a complex-type smoke-suppressing green flame retardant.
[0018] The advantages of the present invention are that the modified ammonium polyphosphate and MOF both have good flame retardant properties, they can work synergistically to significantly improve the thermal stability and flame retardant effect of the flame retardant, the introduction of the metal-modified molecular sieve enhances the flame retardant efficiency of the flame retardant, and each component can be evenly dispersed in the flame retardant through dissolution and stirring in deionized water, avoiding the occurrence of agglomeration and precipitation, which helps to evenly distribute the flame retardant in the polymer material and improves its flame retardant effect.
[0019] Preferably, step (6) preparation of flame retardant and smoke suppressing hollow board core After the veneer is impregnated with the complex type smoke suppression green flame retardant prepared in step (5), it is dried and dried at a temperature of 40-60°C for 15-60 minutes. The treated veneer is then blended with deionized water, the complex type smoke suppression green flame retardant and molecular sieve to prepare a flame retardant and smoke suppression board core. The mixture is stirred in a stirrer at 1150-1200 r / min for 3-6 minutes to fully disperse it. The mixture is placed in a vacuum drying oven and dried at 60-65°C until no water overflows. The dried mixture is cold-pressed in a mold to prepare a board core. The cold pressing pressure is 0.35-0.40 MPa and the time is 1-5 minutes.
[0020] The invention has the advantage that, through the cold pressing process, the board core has excellent physical properties, such as high strength, high toughness, etc.; the cold pressing pressure and time ensure the structural stability and service life of the board core.
[0021] Preferably, step (7) tannin-formaldehyde-furfural resin adhesive is prepared Dissolve tannin powder in 5-10% sodium hydroxide solution to prepare a tannin solution with a concentration of 35-40%, then put the tannin solution into a three-necked flask and heat it at 80-85°C for 0.5-1h; then add 5-8% sodium sulfite by weight of tannin powder to the mixed solution in the three-necked flask, and continue to keep it warm at 80-85°C for 0.5-1.5h; add formaldehyde solution and furfural pretreatment solution to the tannin pretreated solution, and continue to keep it warm at 80-85°C for 0.5-2.0h; then quickly cool the tannin solution to 35-40°C, and obtain tannin-formaldehyde-furfural resin adhesive; The invention has the advantages that the synergistic effect of tannin, formaldehyde and furfural makes the prepared adhesive have excellent bonding strength, will not fail or fall off due to high temperature, does not contain solvents and volatile organic compounds, and will not pollute the environment.
[0022] Preferably, step (8) flame retardant plywood preparation Use the flame retardant and smoke suppressing hollow board core prepared in step (6), add 20-25% of the tannin-formaldehyde-furfural resin adhesive prepared in step (7) (add 5-8ml of 15-20% NH4Cl solution as a curing agent), mix well, then add 50-55g of the complex type smoke suppressing green flame retardant prepared in step (5), mix well, and mold in a 240-250mm×240-250mm wooden mold. Use a 10-15mm thickness gauge to control the thickness of the particle board. Hot press at 180-185℃ and 10-16MPa for 10-12min, then maintain the pressure and cool it to below 40-45℃ with water to release the pressure and take out the board.
[0023] In summary, the present invention has the following beneficial effects: 1. The advantages of the present invention are that zinc nitrate hexahydrate provides metal nodes in the MOF framework, and tetrachloroterephthalic acid coordinates with metal ions to form the MOF framework; chlorine atoms can be arranged in the pores of the MOF as functional groups to regulate the interaction between the MOF and the gas and enhance the stability of the MOF; 2. The present invention has the advantages that controlling the heating rate avoids local overheating or reaction runaway caused by too fast heating, ensures the smooth progress of the reaction, and the prepolymerization temperature control is conducive to the complete melting of urea and avoids possible side reactions at high temperatures. The material is discharged into a white porcelain dish under continuous stirring, which ensures the uniformity and fluidity of the solution and is conducive to the progress of polymerization and curing; 3. The present invention has the advantages that the mixed solution of ethanol and water as a solvent not only provides a good reaction environment, but also helps to evenly mix the raw materials. The oil bath heating ensures the full melting and dispersion of DDM. The reaction conditions are also conducive to the ion exchange reaction between APP and DDM, while avoiding the side reactions that may occur at high temperatures. DDP exhibits excellent flame retardant properties in epoxy resin, and adding a small amount of DDP can significantly reduce the flammability of epoxy resin. 4. The present invention has the advantages that the acidity and adsorption performance of the 5A molecular sieve can be enhanced by grinding and activating the polyphosphoric acid, so that it has higher selectivity and adsorption capacity for specific substances, and the introduction of metal ions can further improve the structural stability of the molecular sieve; the introduction of polyphosphoric acid and metal ions can significantly improve the thermal stability and chemical stability of the 5A molecular sieve, so that it can still maintain good performance in a high temperature environment; 5. The advantages of the present invention are that the modified ammonium polyphosphate and MOF both have good flame retardant properties, they can work synergistically to significantly improve the thermal stability and flame retardant effect of the flame retardant, the introduction of the metal-modified molecular sieve enhances the flame retardant efficiency of the flame retardant, and each component can be evenly dispersed in the flame retardant through dissolution and stirring in deionized water, avoiding the occurrence of agglomeration and precipitation, which helps the flame retardant to be evenly distributed in the polymer material and improves its flame retardant effect; 6. The present invention has the advantage that, through the cold pressing process, the board core has excellent physical properties, such as high strength and high toughness; the cold pressing pressure and time ensure the structural stability and service life of the board core; 7. The advantages of the present invention are that the synergistic effect of tannin, formaldehyde and furfural makes the prepared adhesive have excellent bonding strength, will not fail or fall off due to high temperature, does not contain solvents and volatile organic compounds, and will not pollute the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The invention discloses a process for preparing flame-retardant plywood using a complex type smoke-suppressing green flame retardant. DETAILED DESCRIPTION
[0025] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.
[0026] If not specifically stated, the technical means used in the examples are conventional means known to those skilled in the art. In addition, all the raw materials used in the examples are known commercial products.
[0027] Example 1
[0028] Step (1) Synthesis of MOF Zinc nitrate hexahydrate (7.0 mg, 0.025 mmol), tetrachloroterephthalic acid (10 mg, 0.04 mmol), triethylenediamine (2.0 mg, 0.02 mmol) and DMF (1.0 mL) were dissolved in a 15 mL transparent glass bottle and placed in an oven at 83 °C for 1 day to obtain colorless rhombic crystals. Step (2) Synthesis of ammonium polyphosphate 82% phosphoric acid and 98% urea are added into a three-necked flask in a ratio of 1:1.7 (molar ratio), heated and stirred, and the heating rate is controlled to be no more than 5°C / min. When the temperature rises to the prepolymerization temperature (about 95°C), the urea is completely melted and the solution is clear and bubbling, and a large amount of gas escapes (pH=3 in the early stage and pH=8 in the later stage). After the solution becomes thick and sticky, it is discharged into a white porcelain plate under continuous stirring and placed in a constant temperature oven for polymerization and curing. After the curing is complete, it is cooled to obtain ammonium polyphosphate; Step (3) Synthesis of diaminodiphenylmethane modified ammonium polyphosphate Mix ethanol and water (195 ml:10 ml) and pour them into a three-necked flask. Heat the mixed solution to 90°C in an oil bath and stir for 30 minutes. Then, inject 10 g of molten DDM into the mixed solution. Slowly inject 21 g of the ammonium polyphosphate prepared in step (2) into the three-necked flask and stir at 59°C for 3 hours. After the reaction is completed, cool the mixed solution and filter to obtain a light yellow solid. Wash it with distilled water and ethanol for 3 times respectively, and then dry it at 60°C. Grind and sieve the obtained light yellow solid to obtain diaminodiphenylmethane modified ammonium polyphosphate. Step (4) Modification of 5A molecular sieve The polyphosphoric acid and 5A molecular sieve were respectively placed in a ceramic mortar and ground for 24 minutes, fully ground, passed through a 120-mesh sieve, activated in a muffle furnace at 795°C for 6 hours, and then added with wood powder to continue grinding until fully uniform for use. Metal ion modified molecular sieve: The molecular sieves were soaked in aqueous solutions of different metal salts (the metal element loading was 1% of the mass of the molecular sieve), stirred for 1 hour, and then sanded for 30 minutes using a sand mill / dispersing stirring multi-purpose machine, placed to dry naturally, dried at 100°C for 1 hour, and then placed in a muffle furnace at 550°C for 10 hours to obtain a metal modified molecular sieve; Step (5) Complex type smoke suppression green flame retardant 26 g of the ammonium polyphosphate modified in step (3) and the MOF prepared in step (1) were added to 96 mL of deionized water, and stirred at 31°C until no precipitation was produced; then the metal-modified molecular sieve prepared in step (4), 0.7 g of MC (sodium carboxymethyl cellulose) and 0.6 g of 500Cu-Z (copper-modified molecular sieve) were added in sequence, and further stirred until no precipitation was produced, to obtain a complex-type smoke-suppressing green flame retardant; Step (6) Preparation of flame retardant and smoke suppression hollow board core The veneer is impregnated with the complex type smoke suppression green flame retardant prepared in step (5) and then dried. The veneer is dried at a temperature of 42°C for 20 minutes. The treated veneer is then blended with deionized water, the complex type smoke suppression green flame retardant and the molecular sieve to prepare a flame retardant and smoke suppression board core. The mixture is stirred in a stirrer at 1150 r / min for 3 minutes to fully disperse it. The mixture is placed in a vacuum drying oven and dried at 60°C until no water overflows. The dried mixture is cold pressed in a mold to prepare a board core. The cold pressing pressure is 0.35 MPa and the time is 2 minutes. Step (7) Preparation of tannin-formaldehyde-furfural resin adhesive Dissolve tannin powder in 6% sodium hydroxide solution to prepare a tannin solution with a concentration of 35%, then put the tannin solution into a three-necked flask and heat it at 82°C for 0.5h; then add tannin powder weight 6 and furfural pretreatment liquid to the mixed solution in the three-necked flask, add it to the tannin pretreated solution, and continue to keep it warm at 86°C for 1h; then quickly cool the tannin solution to 42°C, and get the tannin-formaldehyde-furfural resin adhesive; Step (8) Preparation of flame retardant plywood Use the flame retardant and smoke suppression hollow board core prepared in step (6), add 22% of the tannin-formaldehyde-furfural resin adhesive prepared in step (7) (add 6 ml of 16% NH4Cl solution as a curing agent), mix well, then add 53g of the complex type smoke suppression green flame retardant prepared in step (5), mix well, and mold in a 245mm×245mm wooden mold. Use a 10mm thickness gauge to control the thickness of the particle board. Hot press at 180℃ and 10MPa for 10min, then maintain the pressure and cool it to below 40℃ with water to release the pressure and take out the board.
[0029] Example 2 Step (1) Synthesis of MOF Zinc nitrate hexahydrate (7.2 mg, 0.026 mmol), tetrachloroterephthalic acid (13 mg, 0.05 mmol), triethylenediamine (2.0 mg, 0.03 mmol) and DMF (1.0 mL) were dissolved in a 16 mL transparent glass bottle and placed in an oven at 85 °C for 2 days to obtain colorless rhombic crystals. Step (2) Synthesis of ammonium polyphosphate 83% phosphoric acid and 98% urea are added into a three-necked flask in a ratio of 1:1.7 (molar ratio), heated and stirred, and the heating rate is controlled to be no more than 7°C / min. When the temperature rises to the prepolymerization temperature (about 96°C), the urea is completely melted and the solution is clear and bubbling, and a large amount of gas escapes (pH=4 in the early stage and pH=8 in the later stage). After the solution becomes thick and sticky, it is discharged into a white porcelain plate under continuous stirring and placed in a constant temperature oven for polymerization and curing. After the curing is complete, it is cooled to obtain ammonium polyphosphate; Step (3) Synthesis of diaminodiphenylmethane modified ammonium polyphosphate Pour a mixture of ethanol and water (195 ml:10 ml) into a three-necked flask, heat the mixed solution to 90°C in an oil bath and stir for 30 min, then inject 11 g of molten DDM into the mixed solution, slowly inject 21 g of the ammonium polyphosphate prepared in step (2) into the three-necked flask, and stir at 60°C for 4 h. After the reaction is completed, cool the mixed solution, filter to obtain a light yellow solid, wash it twice with distilled water and ethanol respectively, and then dry it at 63°C. Grind and sieve the obtained light yellow solid to obtain diaminodiphenylmethane modified ammonium polyphosphate; Step (4) Modification of 5A molecular sieve The polyphosphoric acid and 5A molecular sieve were respectively placed in a ceramic mortar and ground for 25 minutes, fully ground, passed through a 120-mesh sieve, activated in a muffle furnace at 800°C for 7 hours, and then added with wood powder to continue grinding until fully uniform for use. Metal ion modified molecular sieve: The molecular sieves were soaked in aqueous solutions of different metal salts (the metal element loading was 4% of the molecular sieve mass), stirred for 1 hour, and then sanded for 34 minutes using a sand mill / dispersing stirring multi-purpose machine, placed to dry naturally, dried at 105°C for 2 hours, and then placed in a muffle furnace at 550°C for 10 hours to obtain a metal modified molecular sieve; Step (5) Complex type smoke suppression green flame retardant 26 g of the ammonium polyphosphate modified in step (3) and the MOF prepared in step (1) were added to 97 mL of deionized water, and stirred at 32°C until no precipitation was produced; then the metal-modified molecular sieve prepared in step (4), 0.7 g of MC (sodium carboxymethyl cellulose) and 0.6 g of 500Cu-Z (copper-modified molecular sieve) were added in sequence, and further stirred until no precipitation was produced, to obtain a complex-type smoke-suppressing green flame retardant; Step (6) Preparation of flame retardant and smoke suppression hollow board core The veneer is impregnated with the complex type smoke suppression green flame retardant prepared in step (5) and then dried. The veneer is dried at a temperature of 50°C for 30 minutes. The treated veneer is then blended with deionized water, the complex type smoke suppression green flame retardant and the molecular sieve to prepare a flame retardant and smoke suppression board core. The mixture is stirred in a stirrer at 1200 r / min for 3 minutes to fully disperse it. The mixture is placed in a vacuum drying oven and dried at 62°C until no water overflows. The dried mixture is cold pressed in a mold to prepare a board core. The cold pressing pressure is 0.38 MPa and the time is 4 minutes. Step (7) Preparation of tannin-formaldehyde-furfural resin adhesive Dissolve tannin powder in 8% sodium hydroxide solution to prepare a tannin solution with a concentration of 38%, then put the tannin solution into a three-necked flask and heat it at 85°C for 1 hour; then add sodium sulfite with a basis weight of 8% of tannin powder to the mixed solution in the three-necked flask, and continue to keep it warm at 84°C for 0.5 hour; add formaldehyde solution and furfural pretreatment solution to the tannin pretreated solution, and continue to keep it warm at 85°C for 2.0 hour; then quickly cool the tannin solution to 40°C, and obtain tannin-formaldehyde-furfural resin adhesive; Step (8) Preparation of flame retardant plywood Use the flame retardant and smoke suppression hollow board core prepared in step (6), add 25% of the tannin-formaldehyde-furfural resin adhesive prepared in step (7) (add 6 ml of 15% NH4Cl solution as a curing agent), mix well, then add 54g of the complex type smoke suppression green flame retardant prepared in step (5), mix well, and mold in a 240mm×240mm wooden mold. Use a 15mm thickness gauge to control the thickness of the particle board. Hot press at 183℃ and 13MPa for 11min, then maintain the pressure and cool it to below 43℃ with water to release the pressure and take out the board.
[0030] Example 3
[0031] Step (1) Synthesis of MOF Zinc nitrate hexahydrate (7.5 mg, 0.030 mmol), tetrachloroterephthalic acid (13 mg, 0.08 mmol), triethylenediamine (3.0 mg, 0.05 mmol) and DMF (2.0 mL) were dissolved in a 22 mL transparent glass bottle and placed in an oven at 86 °C for 5 days to obtain colorless rhombic crystals. Step (2) Synthesis of ammonium polyphosphate 86% phosphoric acid and 99% urea are added to a three-necked flask in a ratio of 2:1.8 (molar ratio), heated and stirred, and the heating rate is controlled to be no more than 10°C / min. When the temperature rises to the prepolymerization temperature (about 100°C), the urea is completely melted and the solution is clear and bubbling, and a large amount of gas escapes (pH=6 in the early stage and pH=10 in the later stage). After the solution becomes thick and sticky, it is discharged into a white porcelain plate under continuous stirring and placed in a constant temperature oven for polymerization and curing. After the curing is complete, it is cooled to obtain ammonium polyphosphate; Step (3) Synthesis of diaminodiphenylmethane modified ammonium polyphosphate Pour a mixture of ethanol and water (200 ml:12 ml) into a three-necked flask, heat the mixed solution to 90°C in an oil bath and stir for 35 minutes, then inject 13 g of molten DDM into the mixed solution, slowly inject 24 g of the ammonium polyphosphate prepared in step (2) into the three-necked flask, and stir at 62°C for 5 hours. After the reaction is completed, cool the mixed solution, filter to obtain a light yellow solid, wash it with distilled water and ethanol for 3 times respectively, and then dry it at 65°C. Grind and sieve the obtained light yellow solid to obtain diaminodiphenylmethane modified ammonium polyphosphate; Step (4) Modification of 5A molecular sieve The polyphosphoric acid and 5A molecular sieve were respectively placed in a ceramic mortar and ground for 30 minutes, fully ground, passed through a 120-mesh sieve, activated in a muffle furnace at 800°C for 10 hours, and then added with wood powder to continue grinding until fully uniform for use. Metal ion modified molecular sieve: The molecular sieves were soaked in aqueous solutions of different metal salts (the metal element loading was 5% of the molecular sieve mass), stirred for 2 hours, and then sanded for 35 minutes using a sand mill / dispersing stirring multi-purpose machine, placed to dry naturally, dried at 110°C for 4 hours, and then placed in a muffle furnace at 555°C for 12 hours to obtain a metal modified molecular sieve; Step (5) Complex type smoke suppression green flame retardant 30 g of the ammonium polyphosphate modified in step (3) and the MOF prepared in step (1) were added to 100 mL of deionized water, and the mixture was stirred at 35°C until no precipitation was produced; then the metal-modified molecular sieve prepared in step (4), 0.8 g of MC (sodium carboxymethyl cellulose) and 0.9 g of 500Cu-Z (copper-modified molecular sieve) were added in sequence, and the mixture was further stirred until no precipitation was produced, thereby obtaining a complex-type smoke-suppressing green flame retardant; Step (6) Preparation of flame retardant and smoke suppression hollow board core The veneer is impregnated with the complex type smoke suppression green flame retardant prepared in step (5) and then dried. The veneer is dried at a temperature of 60°C for 60 minutes. The treated veneer is then blended with deionized water, the complex type smoke suppression green flame retardant and the molecular sieve to prepare a flame retardant and smoke suppression board core. The mixture is stirred in a stirrer at 1200 r / min for 6 minutes to fully disperse it. The mixture is placed in a vacuum drying oven and dried at 65°C until no water overflows. The dried mixture is cold pressed in a mold to prepare a board core. The cold pressing pressure is 0.40 MPa and the time is 1 minute. Step (7) Preparation of tannin-formaldehyde-furfural resin adhesive Dissolve tannin powder in 10% sodium hydroxide solution to prepare a tannin solution with a concentration of 40%, then put the tannin solution into a three-necked flask and heat it at 85°C for 1 hour; then add sodium sulfite with a basis weight of 8% of tannin powder to the mixed solution in the three-necked flask, and continue to keep it warm at 82°C for 0.5 hour; add formaldehyde solution and furfural pretreatment solution to the tannin pretreated solution, and continue to keep it warm at 80°C for 0.5 hour; then quickly cool the tannin solution to 40°C, and obtain tannin-formaldehyde-furfural resin adhesive; Step (8) Preparation of flame retardant plywood Use the flame retardant and smoke suppression hollow board core prepared in step (6), add 25% of the tannin-formaldehyde-furfural resin adhesive prepared in step (7) (add 8ml of 20% NH4Cl solution as a curing agent), mix well, then add 55g of the complex type smoke suppression green flame retardant prepared in step (5), mix well, and mold in a 240mm×240mm wooden mold. Use a 10mm thickness gauge to control the thickness of the particle board. Hot press at 185℃ and 16MPa for 10min, then maintain the pressure and cool it to below 45℃ with water to release the pressure and take out the board.
[0032] Example 4
[0033] Step (1) Synthesis of MOF Zinc nitrate hexahydrate (7.4 mg, 0.025 mmol), tetrachloroterephthalic acid (12.2 mg, 0.04 mmol), triethylenediamine (2.3 mg, 0.02 mmol) and DMF (1.5 mL) were dissolved in a 20 mL transparent glass bottle and placed in an oven at 85 °C for 5 days to obtain colorless rhombic crystals; Step (2) Synthesis of ammonium polyphosphate 85% phosphoric acid and 99% urea are added into a three-necked flask in a ratio of 1:1.7 (molar ratio), heated and stirred, and the heating rate is controlled to be no more than 10°C / min. When the temperature rises to the prepolymerization temperature (about 100°C), the urea is completely melted and the solution is clear and bubbling, and a large amount of gas escapes (pH=6 in the early stage and pH=8 in the later stage). After the solution becomes thick and sticky, it is discharged into a white porcelain plate under continuous stirring and placed in a constant temperature oven for polymerization and curing. After the curing is complete, it is cooled to obtain ammonium polyphosphate APP; Step (3) Synthesis of diaminodiphenylmethane modified ammonium polyphosphate Pour a mixture of ethanol and water (200 ml:10 ml) into a three-necked flask, heat the mixed solution to 90°C in an oil bath and stir for 30 min, then inject 10 g of molten DDM into the mixed solution, slowly inject 20 g of the ammonium polyphosphate prepared in step (2) into the three-necked flask, and stir at 60°C for 4 h. After the reaction is completed, cool the mixed solution, filter to obtain a light yellow solid, wash it with distilled water and ethanol for 3 times respectively, and then dry it at 60°C. Grind and sieve the obtained light yellow solid to obtain diaminodiphenylmethane modified ammonium polyphosphate; Step (4) Modification of 5A molecular sieve Place polyphosphoric acid and 5A molecular sieve in a ceramic mortar and grind for 30 minutes, fully grind, pass through a 120-mesh sieve, activate in a muffle furnace at 800°C for 6 hours, add wood powder and continue grinding until fully uniform for use. Metal ion modified molecular sieve: soak the molecular sieve in aqueous solutions of different metal salts (the metal element loading is 5% of the mass of the molecular sieve), stir for 1 hour, then sand grind with a sand grinder / dispersing stirring multi-purpose machine for 30 minutes, place it to dry naturally, dry at 110°C for 4 hours, and then place it in a muffle furnace at 550°C for 10 hours to obtain a metal modified molecular sieve; Step (5) Complex type smoke suppression green flame retardant 25 g of the ammonium polyphosphate modified in step (3) and the MOF prepared in step (1) were added to 100 mL of deionized water, and the mixture was stirred at 30° C. until no precipitation was produced; then the metal-modified molecular sieve prepared in step (4), 0.8 g of MC (sodium carboxymethyl cellulose) and 0.9 g of 500Cu-Z (copper-modified molecular sieve) were added in sequence, and the mixture was further stirred until no precipitation was produced, thereby obtaining a complex-type smoke-suppressing green flame retardant; Step (6) Preparation of flame retardant and smoke suppression hollow board core The veneer is impregnated with the complex type smoke suppression green flame retardant prepared in step (5) and then dried. The veneer is dried at a temperature of 60°C for 50 minutes. The treated veneer is then blended with deionized water, the complex type smoke suppression green flame retardant and the molecular sieve to prepare a flame retardant and smoke suppression board core. The mixture is stirred in a stirrer at 1200 r / min for 3 minutes to fully disperse it. The mixture is placed in a vacuum drying oven and dried at 60°C until no water overflows. The dried mixture is cold pressed in a mold to prepare a board core. The cold pressing pressure is 0.35 MPa and the time is 5 minutes. Step (7) Preparation of tannin-formaldehyde-furfural resin adhesive Dissolve tannin powder in 10% sodium hydroxide solution to prepare a tannin solution with a concentration of 40%, then put the tannin solution into a three-necked flask and heat it at 80°C for 0.5h; then add 8% sodium sulfite by weight of tannin powder to the mixed solution in the three-necked flask, and continue to keep it warm at 80°C for 0.5h; add formaldehyde solution and furfural pretreatment solution to the tannin pretreated solution, and continue to keep it warm at 80°C for 0.5h; then quickly cool the tannin solution to 40°C, and get a tannin-formaldehyde-furfural resin adhesive; Step (8) Preparation of flame retardant plywood Use the flame retardant and smoke suppression hollow board core prepared in step (6), add 20% of the tannin-formaldehyde-furfural resin adhesive prepared in step (7) (add 8 ml of 20% NH4Cl solution as a curing agent), mix well, then add 50g of the complex type smoke suppression green flame retardant prepared in step (5), mix well, and mold in a 240mm×240mm wooden mold. Use a 10mm thickness gauge to control the thickness of the particle board. Hot press at 180℃ and 16MPa for 12min, then maintain the pressure and cool it to below 45℃ with water to release the pressure and take out the board.
[0034] Comparative Example 1
[0035] Step (1) Synthesis of MOF Zinc nitrate hexahydrate (7.9 mg, 0.025 mmol), tetrachloroterephthalic acid (13 mg, 0.08 mmol), triethylenediamine (2.3 mg, 0.02 mmol) and DMF (1 mL) were dissolved in a 25 mL transparent glass bottle and placed in a 95 °C oven for 6 days to obtain colorless rhombic crystals; Step (2) Synthesis of ammonium polyphosphate 95% phosphoric acid and 99% urea are added into a three-necked flask in a ratio of 2:1.7 (molar ratio), heated and stirred, and the heating rate is controlled to be no more than 15°C / min. When the temperature rises to the prepolymerization temperature (about 100°C), the urea is completely melted and the solution is clear and bubbling, and a large amount of gas escapes (pH=6 in the early stage and pH=8 in the later stage). After the solution becomes thick and sticky, it is discharged into a white porcelain plate under continuous stirring and placed in a constant temperature oven for polymerization and curing. After the curing is complete, it is cooled to obtain ammonium polyphosphate APP; Step (3) Synthesis of diaminodiphenylmethane modified ammonium polyphosphate Mix ethanol and water (250ml:15ml) and pour them into a three-necked flask. Heat the mixed solution to 95°C in an oil bath and stir for 60 minutes. Then, inject 15g of molten DDM into the mixed solution. Slowly inject 25g of the ammonium polyphosphate prepared in step (2) into the three-necked flask and stir at 65°C for 2h. After the reaction is completed, cool the mixed solution and filter to obtain a light yellow solid. Wash it twice with distilled water and ethanol respectively, and then dry it at 65°C. Grind and sieve the obtained light yellow solid to obtain diaminodiphenylmethane modified ammonium polyphosphate. Step (4) Complex type smoke suppression green flame retardant 30 g of the ammonium polyphosphate modified in step (3) and the MOF prepared in step (1) were added to 100 mL of deionized water, and the mixture was stirred at 25° C. until no precipitation was produced; then 0.9 g of MC (sodium carboxymethyl cellulose) and 0.9 g of 500 Cu-Z (copper modified molecular sieve) were added in sequence, and the mixture was further stirred until no precipitation was produced, thereby obtaining a complex-type smoke-suppressing green flame retardant; Step (5) Preparation of flame retardant and smoke suppression hollow board core The veneer is impregnated with the complex type smoke suppression green flame retardant prepared in step (4) and then dried. The veneer is dried at a temperature of 65°C for 60 minutes. The treated veneer is then blended with deionized water, the complex type smoke suppression green flame retardant and the molecular sieve to prepare a flame retardant and smoke suppression board core. The mixture is stirred in a stirrer at 1300 r / min for 10 minutes to fully disperse it. The mixture is placed in a vacuum drying oven and dried at 65°C until no water overflows. The dried mixture is cold pressed in a mold to prepare a board core. The cold pressing pressure is 0.45 MPa and the time is 6 minutes. Step (6) Preparation of tannin-formaldehyde-furfural resin adhesive Dissolve tannin powder in 12% sodium hydroxide solution to prepare a tannin solution with a concentration of 40%, then put the tannin solution into a three-necked flask and heat it at 80°C for 0.5h; then add sodium sulfite with a basis weight of 9% of tannin powder to the mixed solution in the three-necked flask, and continue to keep it warm at 85°C for 0.5h; add formaldehyde solution and furfural pretreatment solution to the tannin pretreated solution, and continue to keep it warm at 85°C for 1h; then quickly cool the tannin solution to 45°C, and obtain tannin-formaldehyde-furfural resin adhesive; Step (7) Preparation of flame retardant plywood Use the flame retardant and smoke suppression hollow board core prepared in step (5), add 30% of the tannin-formaldehyde-furfural resin adhesive prepared in step (6) (add 9 ml of 25% NH4Cl solution as a curing agent), mix well, then add 55g of the complex type smoke suppression green flame retardant prepared in step (4), mix well, and mold in a 250mm×240mm wooden mold. Use a 10mm thickness gauge to control the thickness of the particle board. Hot press at 190℃ and 20MPa for 15min, then maintain the pressure and cool it to below 60℃ with water to release the pressure and take out the board.
[0036] Comparative Example 2
[0037] Step (1) Synthesis of MOF Zinc nitrate hexahydrate (5.4 mg, 0.020 mmol), tetrachloroterephthalic acid (10.2 mg, 0.02 mmol), triethylenediamine (2.0 mg, 0.02 mmol) and DMF (1 mL) were dissolved in a 25 mL transparent glass bottle and placed in a 55 °C oven for 4 days to obtain colorless rhombic crystals; Step (2) Synthesis of ammonium polyphosphate 75% phosphoric acid and 89% urea are added into a three-necked flask in a ratio of 1:1.7 (molar ratio), heated and stirred, and the heating rate is controlled to be no more than 5°C / min. When the temperature rises to the prepolymerization temperature (about 95°C), the urea is completely melted and the solution is clear and bubbling, and a large amount of gas escapes (pH=6 in the early stage and pH=8 in the later stage). After the solution becomes thick and sticky, it is discharged into a white porcelain plate under continuous stirring and placed in a constant temperature oven for polymerization and curing. After the curing is complete, it is cooled to obtain ammonium polyphosphate; Step (3) Synthesis of diaminodiphenylmethane modified ammonium polyphosphate Mix ethanol and water (150 ml:5 ml) and pour them into a three-necked flask. Heat the mixed solution to 85°C in an oil bath and stir for 25 minutes. Then, inject 5 g of molten DDM into the mixed solution. Slowly inject 20 g of the ammonium polyphosphate prepared in step (2) into the three-necked flask and stir at 55°C for 3 hours. After the reaction is completed, cool the mixed solution and filter to obtain a light yellow solid. Wash it with distilled water and ethanol for 3 times respectively, and then dry it at 55°C. Grind and sieve the obtained light yellow solid to obtain diaminodiphenylmethane modified ammonium polyphosphate. Step (4) Modification of 5A molecular sieve Place polyphosphoric acid and 5A molecular sieve in a ceramic mortar and grind for 25 minutes, grind thoroughly, pass through a 120-mesh sieve, activate in a muffle furnace at 600°C for 3 hours, add wood powder and continue grinding until it is fully uniform for use. Metal ion modified molecular sieve: soak the molecular sieves in aqueous solutions of different metal salts (the metal element loading is 3% of the mass of the molecular sieve), stir for 2 hours, and then sand grind with a sand grinder / dispersing stirring multi-purpose machine for 25 minutes, place it to air dry naturally, dry at 95°C for 3 hours, and then place it in a muffle furnace at 550°C for 5 hours to obtain the metal modified molecular sieve.
[0038] Step (5) Complex type smoke suppression green flame retardant 15 g of the ammonium polyphosphate modified in step (3) and the MOF prepared in step (1) were added to 100 mL of deionized water, and the mixture was stirred at 25° C. until no precipitation was produced; then the metal-modified molecular sieve prepared in step (4), 0.7 g of MC (sodium carboxymethyl cellulose) and 0.9 g of 500Cu-Z (copper-modified molecular sieve) were added in sequence, and the mixture was further stirred until no precipitation was produced, thereby obtaining a complex-type smoke-suppressing green flame retardant; Step (6) Preparation of flame retardant and smoke suppression hollow board core The veneer is impregnated with the complex type smoke suppression green flame retardant prepared in step (5) and then dried. The veneer is dried at a temperature of 55°C for 45 minutes. The treated veneer is then blended with deionized water, the complex type smoke suppression green flame retardant and the molecular sieve to prepare a flame retardant and smoke suppression board core. The mixture is stirred in a stirrer at 1200 r / min for 2 minutes to fully disperse it. The mixture is placed in a vacuum drying oven and dried at 45°C until no water overflows. The dried mixture is cold pressed in a mold to prepare a board core. The cold pressing pressure is 0.35 MPa and the time is 3 minutes. Step (7) Preparation of flame retardant plywood Use the flame retardant and smoke suppression hollow board core prepared in step (6), add 8 ml of 25% NH4Cl solution as a curing agent and mix well, then add 40 g of the complex type smoke suppression green flame retardant prepared in step (5) and mix well, and shape it in a 240 mm × 240 mm wooden mold, use a 5 mm thickness gauge to control the thickness of the particle board, hot press at 170°C and 16 MPa for 10 min, then maintain the pressure and cool it to below 35°C through water, then release the pressure and take out the board.
[0039] Comparison of detection experiments: The flame retardant plywood obtained in Examples 1 to 4 and Comparative Example Products 1 and 2 were tested. The specific testing method is as follows: Flame retardant performance testing Place the flame-retardant plywood vertically, ignite one end of it with a specified fire source, and observe and record the burning time of the sample. Fix the sample on the test equipment according to the requirements of the test method, ensure that the sample is stable and motionless, use an igniter to ignite one end of the sample, start timing and observe the burning behavior of the sample.
[0040] Formaldehyde emission detection Select a climate chamber that meets the standards, such as a 1 cubic meter climate chamber, to ensure that its interior is clean and dry, and has stable temperature and humidity control capabilities. Set the temperature, humidity, air flow rate, and air replacement rate in the climate chamber as required. The temperature is usually set to (23±0.5)℃, and the relative humidity is set to (50±3)%. Pre-treat the flame-retardant plywood, such as cutting it into small pieces or specified sizes, and ensure that its surface is flat and undamaged. Use formaldehyde-free aluminum tape to seal the edge of the sample to prevent the release of formaldehyde from the edge and affect the test results.
[0041] Smoke suppression performance test Place the test sample on the test equipment, ignite the sample according to the standard requirements, and observe its combustion process. For tests that require the determination of flue gas components, filter paper, filter cartridges, etc. can be used to collect flue gas. The collected flue gas is dried, dissolved, etc., and its components and concentrations are determined using appropriate analytical methods (such as UV-visible absorption spectroscopy, gas chromatography, etc.).
[0042] Table 1 Flame retardant time
[0043] As can be seen from Table 1, Example 4 is the best and Comparative Example 1 is poor. The flame retardant time of Example 4 is longer, and the flame retardant system therein is more stable and more uniform. There is a synergistic effect between the components such as MOF, modified ammonium polyphosphate and metal-modified molecular sieve in Example 4, so that the flame retardant can play a more full role in the combustion process. The plywood prepared therefrom can more effectively prevent the spread of flames and the generation of smoke during the combustion process than the plywood prepared in the comparative example.
[0044] Table 2 Formaldehyde release
[0045] As can be seen from Table 2, Example 4 is the best and Comparative Example 1 is the worst. Example 4 has the least formaldehyde release. Comparative Example 1 uses a higher concentration of phosphoric acid and a faster heating rate, which may lead to a more violent reaction and produce more by-products. Example 4 uses less zinc nitrate hexahydrate and tetrachloroterephthalic acid, but the amount of DMF is relatively large. The synthesis conditions of Example 4 may be more conducive to reducing the production of formaldehyde.
[0046] Table 3 Smoke suppression performance
[0047] As can be seen from Table 3, Example 4 is the best, while Comparative Example 2 is relatively poor. Example 4 has better smoke suppression performance. The flame retardant in Example 4 contains higher quality ammonium polyphosphate and modified ammonium polyphosphate, which can form a more stable and denser carbon layer during the combustion process, thereby more effectively preventing the spread of flames. The flame retardant in Example 4 also adds metal-modified molecular sieves and other smoke suppression components, which can decompose and produce a large amount of water vapor and other non-combustible gases during the combustion process, thereby diluting and suppressing the generation of smoke.
Claims
1. A complex type smoke suppression green flame retardant, characterized in that: include: Step (1) synthesis of MOF, step (2) synthesis of ammonium polyphosphate, step (3) synthesis of diaminodiphenylmethane modified ammonium polyphosphate, step (4) modification of 5A molecular sieve, step (5) complex type smoke suppression green flame retardant, step (6) preparation of flame retardant and smoke suppression hollow board core, step (7) preparation of tannin-formaldehyde-furfural resin adhesive; Wherein, the preparation steps of the complex type smoke suppression green flame retardant in step (5) include: The ammonium polyphosphate modified in step (3) and the MOF prepared in step (1) are added to deionized water and stirred thoroughly until no precipitation is produced; then the metal-modified molecular sieve, MC and 500Cu-Z prepared in step (4) are added in sequence and further stirred until no precipitation is produced, thereby obtaining a complex-type smoke-suppressing green flame retardant.
2. The complex type smoke-suppressing green flame retardant according to claim 1, characterized in that: Step (1) Synthesis of MOF Dissolve zinc nitrate hexahydrate, tetrachloroterephthalic acid, triethylenediamine and DMF together in a transparent glass bottle, place it in an oven and heat it at a constant temperature to obtain colorless rhombus crystals; Step (2) Synthesis of ammonium polyphosphate Phosphoric acid and urea are added to a three-necked flask and heated and stirred. When the temperature reaches the prepolymerization temperature, the urea is completely melted and the solution is clear and bubbling, and a large amount of gas escapes. After the solution becomes thick and sticky, it is discharged into a white porcelain plate under continuous stirring and placed in a constant temperature oven for polymerization and curing. After the curing is complete, it is cooled and crushed to obtain ammonium polyphosphate; Step (3) Synthesis of diaminodiphenylmethane modified ammonium polyphosphate Mix ethanol and water and pour them into a three-necked flask. Heat the mixed solution in an oil bath to a certain temperature and stir. Then, inject molten DDM into the mixed solution. Slowly inject the ammonium polyphosphate prepared in step (2) into the three-necked flask. After the stirring reaction is completed, cool the mixed solution and filter to obtain a light yellow solid. Wash it with distilled water and ethanol respectively, and then dry it. Grind and sieve the obtained light yellow solid to obtain diaminodiphenylmethane modified ammonium polyphosphate. Step (4) Modification of 5A molecular sieve The polyphosphoric acid and 5A molecular sieve are respectively placed in a ceramic mortar and ground, and fully ground. After activation in a muffle furnace, wood powder is added and continued to grind until fully uniform for use; the molecular sieve is placed in a dryer for use. Metal ion modified molecular sieve: the molecular sieve is soaked in aqueous solutions of different metal salts, stirred, and then sanded with a sand mill / dispersing stirring multi-purpose machine, placed to dry naturally, and then placed in a muffle furnace for roasting to obtain a metal modified molecular sieve; Step (5) Complex type smoke suppression green flame retardant Add the ammonium polyphosphate modified in step (3) and the MOF prepared in step (1) into deionized water and stir thoroughly until no precipitation is produced; then add the metal-modified molecular sieve prepared in step (4), MC (sodium carboxymethyl cellulose) and 500Cu-Z in sequence and stir further until no precipitation is produced to obtain a complex-type smoke-suppressing green flame retardant; Step (6) Preparation of flame retardant and smoke suppression hollow board core The veneer is impregnated with the complex type smoke suppression green flame retardant prepared in step (5) and then dried. The veneer after drying is then mixed with deionized water, the complex type smoke suppression green flame retardant and molecular sieve to prepare a flame retardant and smoke suppression board core. The mixture is stirred in a stirrer to be fully dispersed. The mixture is placed in a vacuum drying oven and dried until no water overflows. The dried mixture is cold pressed in a mold to prepare a board core. Step (7) Preparation of tannin-formaldehyde-furfural resin adhesive Dissolve tannin powder in sodium hydroxide solution to prepare tannin solution, then heat the tannin solution in a three-necked flask; add sodium sulfite to the mixed solution in the three-necked flask, keep warm, add formaldehyde solution and furfural pretreatment solution to the tannin pretreated solution, keep warm; cool the tannin solution quickly, and then produce glue to obtain tannin-formaldehyde-furfural resin adhesive.
3. The complex type smoke suppression green flame retardant according to claim 2, characterized in that: Step (1) Synthesis of MOF Dissolve zinc nitrate hexahydrate (7.0-7.5 mg, 0.025-0.030 mmol), tetrachloroterephthalic acid (10-13 mg, 0.04-0.08 mmol), triethylenediamine (2.0-3.0 mg, 0.02-0.05 mmol) and DMF (N,N-dimethylformamide) 1.0-2.0 mL in a 15-22 mL transparent glass bottle, place in an oven at 83-86 ° C and heat at a constant temperature for 1-5 days to obtain colorless rhombus crystals.
4. The complex type smoke-suppressing green flame retardant according to claim 2, characterized in that: Step (2) Synthesis of ammonium polyphosphate 82-86% phosphoric acid and 98-99% urea are sequentially added into a three-necked flask at a ratio of 1-2:1.7-1.8 (molar ratio), heated and stirred, and the heating rate is controlled to be no more than 5-10°C / min. When the temperature reaches the prepolymerization temperature (about 95-100°C), the urea is completely melted, the solution is clear and bubbling, and a large amount of gas escapes (early pH=3-6 and late pH=8-10). After the solution becomes thick and sticky, it is discharged into a white porcelain plate under continuous stirring and placed in a constant temperature oven for polymerization and curing. After the curing is complete, it is cooled to obtain ammonium polyphosphate.
5. The complex type smoke-suppressing green flame retardant according to claim 4, characterized in that: Step (3) Synthesis of diaminodiphenylmethane modified ammonium polyphosphate Mix ethanol and water (195-200ml:10-12ml) and pour them into a three-necked flask. Heat the mixed solution in an oil bath to 85-90°C and stir for 30-35min. Then, inject 10-13g of molten DDM (diaminodiphenylmethane) into the mixed solution. Slowly inject 20-24g of the ammonium polyphosphate prepared in step (2) into the three-necked flask and stir at 58-62°C for 3-5h. After the reaction is completed, cool the mixed solution and filter to obtain a light yellow solid. Wash it with distilled water and ethanol for 1-3 times respectively, and then dry it at 60-65°C. Grind and sieve the obtained light yellow solid to obtain diaminodiphenylmethane modified ammonium polyphosphate.
6. The complex type smoke-suppressing green flame retardant according to claim 5, characterized in that: Step (4) Modification of 5A molecular sieve Place polyphosphoric acid and 5A molecular sieve in a ceramic mortar and grind for 24-30 minutes respectively, grind thoroughly, pass through a 100-120 mesh sieve, activate in a muffle furnace at 795-800°C for 6-10 hours, add wood powder and continue grinding until it is fully uniform for use. Metal ion modified molecular sieve: soak the molecular sieve in aqueous solutions of different metal salts (the metal element loading is 1-5% of the mass of the molecular sieve), stir for 1-2 hours, then sand grind with a sand grinder / dispersing stirring multi-purpose machine for 30-35 minutes, place it to air dry naturally, dry at 100-110°C for 1-4 hours, and then place it in a muffle furnace at 550-555°C for calcination for 10-12 hours to obtain a metal modified molecular sieve.
7. The complex type smoke-suppressing green flame retardant according to claim 6, characterized in that: Step (5) Complex type smoke suppression green flame retardant Add 25-30g of the ammonium polyphosphate modified in step (3) and the MOF prepared in step (1) into 95-100mL of deionized water, and stir thoroughly at 30-35°C until no precipitation is produced; then add the metal-modified molecular sieve prepared in step (4), 0.6-0.8g of MC (sodium carboxymethyl cellulose) and 0.5-0.9g of 500Cu-Z (copper-modified molecular sieve), and further stir until no precipitation is produced to obtain a complex-type smoke-suppressing green flame retardant.
8. The complex type smoke-suppressing green flame retardant according to claim 7, characterized in that: Step (6) Preparation of flame retardant and smoke suppression hollow board core After the veneer is impregnated with the complex type smoke suppression green flame retardant prepared in step (5), it is dried and dried at a temperature of 40-60°C for 15-60 minutes. The treated veneer is then blended with deionized water, the complex type smoke suppression green flame retardant and molecular sieve to prepare a flame retardant and smoke suppression board core. The mixture is stirred in a stirrer at 1150-1200 r / min for 3-6 minutes to fully disperse it. The mixture is placed in a vacuum drying oven and dried at 60-65°C until no water overflows. The dried mixture is cold-pressed in a mold to prepare a board core. The cold pressing pressure is 0.35-0.40 MPa and the time is 1-5 minutes.
9. The complex type smoke-suppressing green flame retardant according to claim 8, characterized in that: Step (7) Preparation of tannin-formaldehyde-furfural resin adhesive Dissolve tannin powder in 5-10% sodium hydroxide solution to prepare a tannin solution with a concentration of 35-40%, then put the tannin solution into a three-necked flask and heat it at 80-85°C for 0.5-1h; then add 5-8% sodium sulfite by weight of tannin powder to the mixed solution in the three-necked flask, and continue to keep warm at 80-85°C for 0.5-1.5h; add formaldehyde solution and furfural pretreatment solution to the tannin pretreated solution, and continue to keep warm at 80-85°C for 0.5-2.0h; then quickly cool the tannin solution to 35-40°C, and obtain tannin-formaldehyde-furfural resin adhesive.
10. A flame-retardant plywood prepared by the complex type smoke-suppressing green flame retardant according to any one of claims 1 to 9, characterized in that: Step (8) Preparation of flame retardant plywood Use the flame retardant and smoke suppressing hollow board core prepared in step (6), add 20-25% of the tannin-formaldehyde-furfural resin adhesive prepared in step (7) (add 5-8ml of 15-20% NH4Cl solution as a curing agent), mix well, then add 50-55g of the complex type smoke suppressing green flame retardant prepared in step (5), mix well, and mold in a 240-250mm×240-250mm wooden mold. Use a 10-15mm thickness gauge to control the thickness of the particle board. Hot press at 180-185℃ and 10-16MPa for 10-12min, then maintain the pressure and cool it to below 40-45℃ with water to release the pressure and take out the board.